VOICES OF DIVERSITY: MULTILINGUALISM AND MULTICULTURALISM IN INDIAN DIASPORIC LITERATURE - Patteti, Raja Sekhar; Rao, Songa Srinivasa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the intertwined themes of multilingualism and multiculturalism within the Indian diaspora and Indian English literary texts. Multilingualism serves as a cornerstone for the Indian diaspora, enabling cultural preservation, social integration, and professional advancement while acting as a bridge between heritage and the host nation’s culture. Similarly, Indian English literature reflects the multicultural ethos of Indian society, addressing themes of identity, coexistence, and the negotiation of cultural plurality. Through works by authors such as Salman Rushdie, Arundhati Roy, Jhumpa Lahiri, and Amitav Ghosh, the literary lens reveals the richness and complexity of India’s diverse sociocultural landscape. The paper examines how multilingualism and multiculturalism, though celebrated, also face challenges such as linguistic attrition, generational shifts, and social tensions, underscoring the need for sustained efforts in preserving these facets in a globalized world.